Browsing makes you feel less bad: An ecological momentary assessment of passive Qzone use and young women's negative emotions. (March 2022) - Yin, Xue-Qin; Zhang, Xin-Xue; Sebastian, Scherr; Wang, Jin-Liang
Highlights: Passive Qzone use was positively associated with reduced negative emotions in Chinese female students during one week. No evidence of moderating effects of self-esteem and life satisfaction on the momentary relationship between passive Qzone use and negative emotions. Findings emphasized the importance of distinguishing short and long-term relationship between social media use and negative emotions. Abstract: Passively browsing other's content on social networking sites (SNS) is popular among young females. It remains unclear how passive use relates to female's negative emotions, and especially whether short-term associations are confined by individual differences. This study used ecological momentary assessment over the course of one week to examine the associations between passive use of SNS and negative emotions, and investigated whether individual differences (i.e., self-esteem and life satisfaction) would moderate this relationship. A sample of N = 99 Chinese female undergraduates ( Mage = 18.81, SD age = 0.84) completed a baseline online survey on self-esteem and life satisfaction, and received a daily online survey about their Qzone use as well as their negative emotions for seven days. Multilevel modeling revealed that passively browsing Qzone on a given day was associated with less negative emotions. However, the within-person association was independent of self-esteem and life satisfaction. Implications of passive SNS use are discussed especially regarding their potential to reduce negative feelings among Chinese young female undergraduate students, at least in the short term.